PENGARUH BUKU SAKU TERHADAP PENGETAHUAN MALARIA PADA IBU HAMIL DI WILAYAH PUSKESMAS GENYEM - Muji Lestari; Fachri Amal (NHM PRESS, 2022)
Background: 11 million pregnant women in 38 countries are infected with malaria. The purpose of this study was to determine the effect of pocket books on malaria knowledge in pregnant women. This type of research uses a quasy experiment with one group pretest posttest. The number of samples is 30 with the sampling technique being total sampling. Data analysis using Paired t test. The results of the study obtained a value of 0.000 (<0.05) the mean pre-test of knowledge before being given a pocket book. The mean value of pre-test knowledge was 55.30 and the mean post-test knowledge was 58.90. Suggestions for the Genyem Health Center to provide a pocket book to every pregnant woman who comes to check her pregnancy. It is for health workers, especially midwives, to use pocket books as KIE media in carrying out their duties.